Assessment of factors affecting micro entrepreneurs in servicing their loan: A case of PRIDE - Bwire, Baraka (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for the award of Master’s degree of Business Administration in Cooperate Management (MBA CM) of Mzumbe University